2015
DOI: 10.1002/cae.21682
|View full text |Cite
|
Sign up to set email alerts
|

Final‐year projects using open source OpenEEG

Abstract: -This paper describes undergraduate electroencephalography projects using the OpenEEG platform. The projects applied a broad range of curriculum components including computer interfacing, signal processing and software development. Project applications were wide-ranging and provided opportunities to explore research areas such as Brain-Computer Interfacing , affective computing and assistive technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…As a result of the measurements conducted via 15 channels, it is observed that the EEG signals can be measured successfully, the obtained EEG signals are compatible with those given in the literature, and the moment of fist-clenching can be detected. Results clearly show that the obtained signals can be used in HCI and BCI systems (Hu et al, 2015;Collins et al, 2016;Cavanagh et al, 2017;Gordleeva et al, 2020;Hooda et al, 2020).…”
Section: Measurement and Evaluation Of Eeg Signalsmentioning
confidence: 87%
See 1 more Smart Citation
“…As a result of the measurements conducted via 15 channels, it is observed that the EEG signals can be measured successfully, the obtained EEG signals are compatible with those given in the literature, and the moment of fist-clenching can be detected. Results clearly show that the obtained signals can be used in HCI and BCI systems (Hu et al, 2015;Collins et al, 2016;Cavanagh et al, 2017;Gordleeva et al, 2020;Hooda et al, 2020).…”
Section: Measurement and Evaluation Of Eeg Signalsmentioning
confidence: 87%
“…Although there have been given EEG, EMG, EOG, EEG-EMG, EOG-EMG-based biosignal data capture applications developed for commercial or academic purposes in the literature, there isn't any study that allows the simultaneous evaluation of EEG, EMG, EOG and ECG biosignals together (Collins et al, 2016;Balamurugan et al, 2020;Teng et al, 2020). Researchers working in the field of biosignal processing and HCI may also prefer to work with data they have purchased from database banks or accessed from open-source databases, due to difficulties and costs of obtaining biosignals from different sources (Cavanagh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Collins et al introduced the OpenEEG project to 3rd and 4th year engineering students to teach hardware and software systems used in EEG signal acquisition and increase interest in brain-computer interfaces (BCI). When surveyed, OpenEEG increased student interest in EEG signals [6]. Suzuki et al created an experiment to measure ECG signals in undergraduate biomedical laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…These platforms have gained popularity in other engineering fields for developing both applications and educational frameworks. Formally, academic educational research related to Robotics [10][11], Architecture [12], Electronics [13][14] and Control engineering [15][16] similarly prove an increasing record of academic activity in several other engineering fields with particular educational targets.…”
Section: Introductionmentioning
confidence: 99%